2003
DOI: 10.1046/j.1365-294x.2003.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Glacial refugia, haplotype distributions, and clonal richness of the Daphnia pulex complex in arctic Canada

Abstract: As part of a large international Arctic biodiversity expedition (Tundra Northwest '99), we examined the distribution of members of the arctic Daphnia pulex complex (Cladocera, Anomopoda) from 121 tundra ponds, spread across 16 sites spanning a large portion of arctic Canada (i.e. from 62 degrees 22' N to 79 degrees 01' N; 66 degrees 45' W to 139 degrees 37' W). Using allozyme electrophoresis and mitochondrial (mt)DNA analyses, we examined the population genetic (clonal) structure of these populations. The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 41 publications
8
64
1
Order By: Relevance
“…Genetic diversity values found for the three studied populations were similar and within the range of other studies with Daphnia populations. Specifically, Nei's genetic diversity index in the present study ranged from 0.33 ± 0.16 to 0.36 ± 0.08 (mean ± standard deviation) while other studies with Daphnia populations reported values of 0.22 (Haag et al, 2005(Haag et al, , 2006 and from 0.10 to 0.50 (Weider and Hobaek, 2003). The values of observed heterozygosity here found ranged from 0.30 to 0.35, which were within the range of reported values of 0.42 ± 0.21 to 0.59 ± 0.28 (Giessler, 1997) and from 0.20 to 0.32 (Limburg and Weider, 2002).…”
Section: Population Genetic Diversitycontrasting
confidence: 72%
“…Genetic diversity values found for the three studied populations were similar and within the range of other studies with Daphnia populations. Specifically, Nei's genetic diversity index in the present study ranged from 0.33 ± 0.16 to 0.36 ± 0.08 (mean ± standard deviation) while other studies with Daphnia populations reported values of 0.22 (Haag et al, 2005(Haag et al, , 2006 and from 0.10 to 0.50 (Weider and Hobaek, 2003). The values of observed heterozygosity here found ranged from 0.30 to 0.35, which were within the range of reported values of 0.42 ± 0.21 to 0.59 ± 0.28 (Giessler, 1997) and from 0.20 to 0.32 (Limburg and Weider, 2002).…”
Section: Population Genetic Diversitycontrasting
confidence: 72%
“…One temperate clone of Daphnia pulex was isolated in 1998 from a shallow pond at Nieuwersluis (The Netherlands: latitude 52°) and was cultured in laboratory prior to experiments. In 1998, polar Daphnia pulicaria was isolated from a pond close to Ny-Å lesund (Svalbard: latitude 79°; species have been identified according to Weider and Hobaek 2003). Microsatellite screening confirmed that the clone was polyploid as has previously also been inferred by the prevalence of unbalanced polymorphism (unpubl.…”
Section: Animalsmentioning
confidence: 76%
“…At Nordenskioldkysten, 23-27 individuals of Daphnia from each pond were randomly collected and stored in 80% ethanol, after which the species composition was determined according to Weider and Hobaek (2003).…”
Section: Sampling Of Pondsmentioning
confidence: 99%